Perspectives on metanarrative as a way of factoring complexity into health services: research synthesis for transforming seniors' care in Canada. (August 2012) - McElhaney, Janet E; Borycki, Elizabeth; Briggs, Marion CE; Bisaillon, Susan; Upshur, Ross; Rockwood, Kenneth
There is a critical need to improve functional outcomes in hospitalized seniors for both the individual and their caregivers, and to plan for a sustainable healthcare system in the face of an aging population. Over 50% of acute care hospital beds in Canada are occupied by seniors; one-third of these older patients will be discharged at a significantly reduced level of functional ability. Most will never recover to their previous level of independence. This article offers perspectives on research and implementation strategies that take into account the complex, interacting challenges to improving hospital outcomes in seniors. To this end, we describe two cost-neutral strategies with demonstrated successful outcomes. One developed as a focused care strategy and related care processes on a geriatric medicine/rehabilitation unit. The other describes a change in staff-mix and hours of interdisciplinary coverage that resulted in increased hours of direct care and improved outcomes for older adults on acute care units. Both strategies demonstrated reductions in length of stay in the initial context; however, we identified a number of challenges to translating these strategies to a broader context. We contend that this difficulty is understandable given the complexity of seniors' health, health services and organizational change. Research methods and approaches to change in health service delivery need to take complexity into account. We propose a metanarrative research methodology that combines qualitative and quantitative methods, as one way of taking complexity into account in health service research. Finally, we propose a way of thinking about organizational change that offers an alternative to typical 'roll-out' strategies that cannot take into account the inevitable uniqueness of each context in which a strategy may be implemented.